Review of the pseudoscorpion genus Stenohya Beier, 1967 from China (Pseudoscorpiones, Neobisiidae) - Jiaqi Zhao; Xiangbo Guo; Zhizhong Gao; Feng Zhang (European Journal of Taxonomy)
Stenohya Beier, 1967 is an Asian pseudoscorpion genus, with more than half of the species reported from China. In this study, eight new Stenohya species from China are described: S. biverticis Zhao, Guo & Zhang sp. nov., S. cordata Zhao, Guo & Zhang sp. nov., S. margarita Zhao, Guo & Zhang sp. nov., S. polygonia Zhao, Guo & Zhang sp. nov. and S. ungulata Zhao, Guo & Zhang sp. nov. from Guangxi, S. jiaxiani Zhao, Guo & Zhang sp. nov. from Fujian, S. harveyi Zhao, Guo & Zhang sp. nov. from Yunnan, and S. qianlei Zhao, Guo & Zhang sp. nov. from Chongqing. The females of S. jiahensis Li & Shi, 2023 and S. dongtianensis Li & Shi, 2023 are described for the first time, and S. bomica Zhao & Zhang, 2011 and S. hainanensis Guo & Zhang 2016 are redescribed based on the reexamination of the type specimens. A key and a distribution map to the Chinese species are provided.